Nitrate adsorption by fired clay in fixed bed column - shahad ali; Ali J. Jaeel (Wasit Journal of Engineering Sciences)
Excessive use of nitrogen fertilizers has increased nitrate concentrations in groundwater, which poses a health hazard from nitrate-contaminated drinking water and contributes to eutrophication. Nitrate removal from water systems has been carefully studied; However, new, low-cost solutions are urgently needed. Clay and terracotta minerals are commonly used in environmental applications due to their non-toxicity, global availability, low cost, and physical and chemical properties (ion-exchange capacity, high surface area, high adsorption, and catalytic properties). Although most are used to reduce cationic pollutants, depending on the method of modification or the materials with which they are mixed, they can be equally effective in removing anionic contamination. The goal of the study is to treat water containing excessive concentrations of nitrates to produce water of acceptable environmental specifications and to evaluate the performance of fired clay as a low-cost and environmentally friendly water treatment material.